2020
DOI: 10.1101/2020.02.03.932806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The key to complexity in interacting systems with multiple strains

Abstract: Ecological community structure, persistence and stability are shaped by multiple forces, acting on multiple scales. These include patterns of resource use and limitation, spatial heterogeneities, drift and migration. Pathogen strains co-circulating in a host population are a special type of an ecological community. They compete for colonization of susceptible hosts, and sometimes interact via altered susceptibilities to co-colonization. Diversity in such pairwise interaction traits enables the multiple strains… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…By (3.1), taking R 0 → 1 + or k → 0 + , which implies µ → ∞, makes the nonlinear part tends to 0, which leads to the competitive exclusion. This remark coincides with the result about µ = 1 (R0−1)k in Gjini and Madec (2021a).…”
Section: What Determines Competitive Exclusion?supporting
confidence: 91%
See 1 more Smart Citation
“…By (3.1), taking R 0 → 1 + or k → 0 + , which implies µ → ∞, makes the nonlinear part tends to 0, which leads to the competitive exclusion. This remark coincides with the result about µ = 1 (R0−1)k in Gjini and Madec (2021a).…”
Section: What Determines Competitive Exclusion?supporting
confidence: 91%
“…6.4 Dynamical transitions: from N = 2 to the N -strain network Throughout this study, we have shown explicitly and illustrated in detail how global parameters of the neutral model, embedded in the center of the dynamics, can shift qualitatively and quantitatively the net competitive outcome for any given pair of strains. Recall that the N = 2 system forms the basic unit in the full competitive network among an arbitrary number N of strains, and that qualitative shifts in each network 'edge', as a function of global parameters, can have far-reaching effects on the collective dynamics among multiple strains, even when strains differ just in co-colonization interactions (Gjini and Madec, 2021a). Having exposed further nonlinear gradient effects of µ, R 0 , k, γ, r in the more complete 2-strain system with variation along 5 fitness dimensions, opens the way towards deeper analysis of their higher-level effects on the N − strain dynamics and coexistence (Le et al, 2021).…”
Section: Effects Of Host Demography On 2-strain Competitionmentioning
confidence: 99%
“…General structures of co-colonization interactions between N species yield coexistence scenarios of more complex nature than fixed points, including limit cycles and chaos [12]. Thus, depending on how frequency dynamics unfold, subject to intrinsic or extrinsic drivers, Q dynamics can be higher or lower, monotonic or oscillatory, and feed back on the system, in a fully analytically-explicit manner (Table 1).…”
Section: Colonization Resistance: System Vs Outsider Speciesmentioning
confidence: 99%
“…It is precisely the analytical tractability of this model [21,12] that makes it easier to study global perturbation effects, and to interpolate across conditions (Table 1). Perturbations affecting global context, such as R 0 and k, directly change the mutual invasion fitnesses λ j i , and thus species dynamics.…”
Section: Antibiotics Can Change Colonization Resistance and Effect Dementioning
confidence: 99%
See 1 more Smart Citation